Supporting Birthing People and Supporting Doulas: The Impact of the COVID-19 Pandemic on a Community-Based Doula Organization in San Francisco (Mary Ann Liebert, 2023)
Background: Beginning in March 2020, health care systems in the United States restricted the number of support people who could be present during pregnancy-related care to reduce the spread of COVID-19. We aimed to describe how SisterWeb, a community-based doula organization that employs Black, Pacific Islander, and Latinx doulas in San Francisco, California, adapted to the COVID-19 pandemic. Methods: As part of process and outcome evaluations conducted through an academic-community partnership, we interviewed SisterWeb doulas, mentors, and leaders in 2020, 2021, and 2022 (n=26 interviews). We identified preliminary themes using the Rapid Assessment Process and then conducted thematic analysis of data related to COVID-19. Results: SisterWeb leadership remained committed to safeguarding doulas by shifting to virtual support until doulas were onboarded as benefitted employees. Doulas reported hospital policies impacted clients' pregnancy-related care. Initially, doulas adapted to virtual support by connecting with clients more frequently through phone and text. When permitted to meet in person, doulas adjusted to client preference. Finally, as the pandemic impacted doulas' well-being, they turned to mentors for emotional support. Discussion and Health Equity Implications: This analysis contributes to a growing body of literature describing doulas' experiences during the pandemic. By shifting to virtual support, SisterWeb leaders prioritized the health, safety, and financial stability of doulas, who were members of communities disproportionately impacted by COVID-19. Our findings suggest that public health guidance, organizational COVID-19 precautions, and hospital policies hindered SisterWeb's goal of ensuring clients receive equitable medical care. In addition, we found that emotional support for doulas is vital to their work.